DIFFERENTIAL EQUATIONS IN ECONOMIC PROBLEMS USING MATHEMATICAL MODELS (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article examines the application of differential equations in economic problems, and also examines models of processes and demand functions using differential equations with separable and separated variables. The article shows how to make differential equations for solving economic problems and making their models. Also, the article shows examples of economic problems and their models.